2021
DOI: 10.1515/jbcpp-2020-0478
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the exposure time to mobile devices and the prevalence of evaporative dry eyes as one of the symptoms of computer vision syndrome among Senior High School students in East Java, Indonesia

Abstract: Objectives Computer vision syndrome (CVS) is a group of various eye and vision-related problems from prolonged use of mobile devices. Symptoms include dry eyes, blurred vision, eye strain, headache, and also neck and shoulder pain. This study was carried out to analyze the correlation between the exposure time of High Energy Visible (HEV) from mobile devices’ use and the prevalence of evaporative dry eyes in young age. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 16 publications
3
7
0
2
Order By: Relevance
“…The authors of [ 26 ] also reported blurred vision and eye redness among medicine students. Other studies [ 27 , 28 ] reported eye dryness as one of the symptoms of CVS. Therefore, on the basis of evidence from the literature and the current study, it can be concluded that the probability of occurrence of eye symptoms in children with CVS is high.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of [ 26 ] also reported blurred vision and eye redness among medicine students. Other studies [ 27 , 28 ] reported eye dryness as one of the symptoms of CVS. Therefore, on the basis of evidence from the literature and the current study, it can be concluded that the probability of occurrence of eye symptoms in children with CVS is high.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Dubai indicated a significant association between screen time of >6 h per day and DED [ 19 ]. A recent study taken among high school students in East Java, Indonesia investigated the impact of mobile devices on evaporative DED and reported that the risk of developing evaporative DED could be induced even with a minimal use of these devices [ 46 ]. However, a study conducted in Saudi Arabia did not find a significant impact of longer electronic device use on increased computer vision syndrome symptoms among health sciences students [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eye strain was found in 18% of teenage students at the end of the day after working on digital devices 10. A study from Indonesia reported that 87.2% of high school students experienced evaporative dry eye, which is one of the risk factors of CVS 16. On average, children aged 8–12 years in the USA were found to spend 4–6 hours a day watching or using screens, while teens spent up to 9 hours 17.…”
Section: Introductionmentioning
confidence: 99%